Femtosecond laser-assisted versus phacoemulsification cataract surgery (FEMCAT): a multicentre participant-masked randomised superiority and cost-effectiveness trial. Issue 10219 (18th January 2020) - Schweitzer, Cedric; Brezin, Antoine; Cochener, Beatrice; Monnet, Dominique; Germain, Christine; Roseng, Stephanie; Sitta, Remi; Maillard, Aline; Hayes, Nathalie; Denis, Philippe; Pisella, Pierre-Jean; Benard, Antoine; et al.
Summary: Background: Cataract surgery is one of the most common operations in health care. Femtosecond laser-assisted cataract surgery (FLACS) enables more precise ocular incisions and lens fragmentation than does phacoemulsification cataract surgery (PCS). We hypothesised that FLACS might improve outcomes in cataract surgery compared with PCS despite having higher costs. Methods: We did a participant-masked randomised superiority clinical trial comparing FLACS and PCS in two parallel groups (permuted block randomisation stratified on centres via a centralised web-based application, allocation ratio 1:1, block size of 2 or 4 for unilateral cases and 2 or 6 for bilateral cases). Five French University Hospitals enrolled consecutive patients aged 22 years or older who were eligible for unilateral or bilateral cataract surgery. Participants, outcome assessors, and technicians carrying out examinations were masked to the surgical treatment allocation until the last follow-up visit and a sham laser procedure was set up for participants randomly assigned to the PCS arm. The primary clinical endpoint was the success rate of surgery, defined as a composite of four outcomes at a 3-month postoperative visit: absence of severe perioperative complication, a best-corrected visual acuity (BCVA) of 0·0 LogMAR (logarithm of the minimum angle of resolution) or better, an absolute refractive error of 0·75 dioptres or less, and unchanged postoperative corneal astigmatism power (≤0·5 dioptres) and axis (≤20°). The primary economic endpoint was the incremental cost per additional patient who had treatment success at 3 months. Primary outcomes were assessed in all randomly assigned patients who met all eligibility criteria (missing data considered as failure). We used mixed logistic regression models or mixed linear regression models for statistical comparisons, adjusted on centres and whether cataract surgery was bilateral or unilateral. The study is registered with ClinicalTrials.gov, NCT01982006 . Findings: Of the 907 patients (1476 eyes) randomly assigned between Oct 9, 2013, and Oct 30, 2015, 870 (704 eyes in FLACS group and 685 eyes in the PCS group) were analysed. We identified no significant difference in the success rate of surgery between the FLACS and PCS groups (FLACS: 41·1% [289 eyes]; PCS: 43·6% [299 eyes]); adjusted odds ratio 0·85, 95% CI 0·64–1·12, p=0·250). The incremental cost-effectiveness ratio was €10 703 saved per additional patient who had treatment success with PCS compared with FLACS. We observed no severe adverse events during the femtosecond laser procedure, and most of the complications in the FLACS group related to the primary outcome measures occurred during the phacoemulsification phase or postoperatively. Interpretation: Despite its advanced technology, femtosecond laser was not superior to phacoemulsification in cataract surgery and, with higher costs, did not provide an additional benefit over phacoemulsification for patients or health-care systems. Funding: French Ministry of Social Affairs and Health.